Dampak Kebakaran HutanTerhadap Sifat Fisika dan Sifat Kimia Tanah di Kabupaten Samosir - Purnama Sari Sagala; Deni Elfiati; Delvian Delvian (Program studi Kehutanan USU, 2015)
Forest damage caused by forest fires could make a great harm. This result aims to determine the impact of forest fires on the physical and chemical properties of soil. The research was conducted in May-July 2014. The soil samples were taken in Samosir, North Sumatra. The method used on this result is zig-zag method. Soil analysis carried out in the Central Laboratory of the Faculty of Agriculture, University of North Sumatra. The results showed that forest fire is not give impact on the physical and chemical properties of soil,because of the type of fires are crown fire.Keywords: Crown fires, the impact, the physical properties of soil, soil chemical properties